Chromatin remodeling at DNA double-strand breaks - Price, Brendan D; D'Andrea, Alan D (Cell, 2013)
DNA double-strand breaks (DSBs) can arise from multiple sources, including exposure to ionizing radiation. The repair of DSBs involves both posttranslational modification of nucleosomes and concentration of DNA-repair proteins at the site of damage. Consequently, nucleosome packing and chromatin architecture surrounding the DSB may limit the ability of the DNA-damage response to access and repair the break. Here, we review early chromatin-based events that promote the formation of open, relaxed chromatin structures at DSBs and that allow the DNA-repair machinery to access the spatially confined region surrounding the DSB, thereby facilitating mammalian DSB repair.